Answer to Question #231585 in Differential Equations for Anu

Question #231585
Dx/y^2+z^2-x^2=dy/-2xy=dz/-2xy
1
Expert's answer
2021-09-01T12:58:16-0400

From the equation "\\frac{dy}{-2xy}=\\frac{dz}{-2xy}" we can deduce that "dy=dz" and that the function "f_1=y-z" is the first integral of the given system.

Consider now the first equation "\\frac{dx}{y^2+z^2-x^2}=\\frac{dy}{-2xy}".

(1) "0=2xydx+dy(y^2+z^2-x^2)=y^2 \\left( \\frac{2xydx-x^2dy}{y^2} +(1+\\frac{z^2}{y^2})dy\\right)"

But

(2) "\\frac{2xydx-x^2dy}{y^2}=d(x^2\/y)"

(3) "(1+\\frac{z^2}{y^2})dy=(1+\\frac{(y-f_1)^2}{y^2})dy=(2-\\frac{2f_1}{y}+\\frac{f_1^2}{y^2})dy="

"=d(2y-2f_1\\log |y|-f_1^2\/y)"

Substituting eq.(2),(3) into eq.(1), we obtain "d(x^2\/y+2y-2f_1\\log |y|-f_1^2\/y)=0"

Therefore the function "f_2=x^2\/y+2y-2(y-z)\\log |y|-(y-z)^2\/y" is also the integral of the given system.

"df_1\\wedge df_2=df_1\\wedge d(x^2\/y)+df_1\\wedge d (2y-2f_1\\log |y|-f_1^2\/y)="

"df_1\\wedge d(x^2\/y)+(1+\\frac{z^2}{y^2})df_1\\wedge dy="

"y^{-2}df_1\\wedge (2xydx+(y^2+z^2-x^2)dy)\\ne 0" inside the open dense set

"U=\\{(x,y,z)\\in\\mathbb{R}^3:xy(y^2+z^2-x^2)\\ne0\\}".

Therefore, the functions "f_1" and "f_2" are functionally independent in "U", and the complete integral for the given system in the domain "U" can be given by the formula "\\Phi(f_1,f_2)" with an arbitrary smooth function "\\Phi".

Answer. "\\Phi(y-z, x^2y^{-1}+2y-2(y-z)\\log |y|-y^{-1}(y-z)^2)" is the complete integral.


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog